The Influence of Customer Experience and Brand Awareness on Customer Loyalty Mediated by Customer Satisfaction (Empirical Study: Yoshinoya Restaurant Customers in DKI Jakarta) - Arvian Yoel Tanudjaja; Liem Bambang Sugiyanto (Journal Research of Social Science, Economics, and Management, 2023)
Objective of research is to investigate the effect of customer experience and brand awarness on customer loyalty among Yoshinoya restaurant customers in DKI Jakarta, both directly and indirectly with mediation of customer satisfaction. This study use quantitative approach. A survey was conducted with 171 respondents who had consumed products of Yoshinoya restaurants in DKI Jakarta. Data analysis was performed using Structural Equation Model with AMOS program. The research findings indicate that the customer experience provided by Yoshinoya restaurants does not have a strong and significant relationship with customer loyalty of Yoshinoya restaurant customers in DKI Jakarta. However, it was found that brand awareness has a strong and significant influence on customer loyalty of Yoshinoya restaurant customers in DKI Jakarta. When mediated by customer satisfaction, turns out customer experience does have a strong and significant relationship with customer loyalty. Enhanced, when brand awareness mediated by customer satisfaction, has a stronger and more significant influence on customer loyalty of Yoshinoya restaurant customers in DKI Jakarta. The implications of this research suggest that companies can enchance customer loyalty by improving customer experience, brand awareness, and customer satisfaction. This can be achieved through the provision of high-quality food, efficient service in terms of speed, a strong brand, and most importantly ensuring customer satisfaction. Customer satisfaction is crucial in transforming a negative into a more positive one.